Rekonfigurasi Jaringan Distribusi Radial Di Penyulang Purwoasri Berbasis Modified Imperialist Competitive Algorithms (MICA) - Yoga Arie Pambayun; Machrus Ali; Hidayatul Nurohmah; Rukslin Rukslin; Achmad Zaini (Jurnal FORTECH, 2020)
Radial distribution network configuration is difficult to simplify because it is very complex. This network reconfiguration is used to redesign the configuration form of the radial distribution network by opening and closing switches on the distribution network. Purwoasri feeders, Rayon Kertosono, Mojokerto area have very large losses that need to be reconfigured. The resulting power flow will produce a network power loss as a result of the configuration. The reconfiguration process will be repeated until the configuration form that produces the smallest power loss is obtained. The number of feeders and buses on the network will be difficult if done with manual calculations and requires a very long time, so solving the problem must use a computer program. Network reconfiguration using the Matlab 2013a program will analyze its power flow using the Newton Raphson method and using the artificial intelligence method, Modified Imperialist Competitive Algorithms (MICA). With this method, it was obtained before the reconfiguration of the network suffered a loss of 89,724 kWatt after the reconfiguration had a loss of 54.8299 kWatt. The results of reconfiguration can reduce losses of 0.6173 kWatt or 38.95688%.